2002
DOI: 10.1139/b02-034
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenosides as host resistance factors in American ginseng (Panax quinquefolius)

Abstract: American ginseng (Panax quinquefolius L.) produces a number of saponins (ginsenosides). The ability of saponins from cultivated American ginseng to inhibit fungal growth in vitro was evaluated. Fungi exhibited a range of sensitivity to ginsenosides extracted from roots collected in two growing seasons. Important root pathogens (Cylindrocarpon destructans, Fusarium solani, and Fusarium oxysporum) were unaffected by these phytochemicals at a concentration of 1 mg·mL -1 , whereas the growth of Alternaria panax an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…can be particularly aggressive towards American ginseng roots with Rb 1 synthesized as a resistance-compound. Nicol et al reported that the mycelium growth of F. oxysporum can be inhibited by crude ginseng saponin extraction (Nicol et al 2002). Our study is the first to determine the effect of mono-ginsenoside on the conidium germination rate of two species of Fusarium spp.…”
Section: Discussionmentioning
confidence: 73%
“…can be particularly aggressive towards American ginseng roots with Rb 1 synthesized as a resistance-compound. Nicol et al reported that the mycelium growth of F. oxysporum can be inhibited by crude ginseng saponin extraction (Nicol et al 2002). Our study is the first to determine the effect of mono-ginsenoside on the conidium germination rate of two species of Fusarium spp.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, the major secreted ginsenosides in the rhizosphere have allelopathic effects on the soil fungal community. The possible mechanism in blocking pathogen attacks is that ginsenosides interact with fungal membrane sterols, leading to damage in membrane integrity Morrissey and Osbourn, 1999;Nicol et al, 2002;Sung and Lee, 2008). On the other hand, the fungitoxic properties of ginsenosides can be attenuated through enzymatic degradation by pathogen-formed glycosidases , and the degraded ginsenosides may subsequently serve as allelopathic growth stimulators of more virulent root pathogens, such as Fusarium spp., and Cylindrocarpon destructans (Nicol et al, 2002;Yousef and Bernards, 2006), implying the evolutionary interaction between ginsenosides rhizosphere and soil fungi has decided for defense or susceptibility.…”
Section: Dynamics Of Ginsenoside Accumulation and The Physiological Fmentioning
confidence: 99%
“…The possible mechanism in blocking pathogen attacks is that ginsenosides interact with fungal membrane sterols, leading to damage in membrane integrity Morrissey and Osbourn, 1999;Nicol et al, 2002;Sung and Lee, 2008). On the other hand, the fungitoxic properties of ginsenosides can be attenuated through enzymatic degradation by pathogen-formed glycosidases , and the degraded ginsenosides may subsequently serve as allelopathic growth stimulators of more virulent root pathogens, such as Fusarium spp., and Cylindrocarpon destructans (Nicol et al, 2002;Yousef and Bernards, 2006), implying the evolutionary interaction between ginsenosides rhizosphere and soil fungi has decided for defense or susceptibility. Moreover, ginsenosides were also shown to have potential anti-insect activity (Mallvadhani et al, 2003), possibly via interfering with the receptor of insect hormone ecdysteroid, and influencing the life cycle of herbivorous insects (Harada et al, 2009).…”
Section: Dynamics Of Ginsenoside Accumulation and The Physiological Fmentioning
confidence: 99%
“…34,35 Further mechanistic studies revealed that the total ginsenosides reduced the protein content and the activity of digestive enzymes, 36 inhibited the activities of acetylcholinesterase and glutathione s-transferase, 34 and disturbed the original dynamic balance of protective enzymes (e.g., superoxide dismutase, chloramphenicol acetyltransferase, and peroxidases). 37 The crude ginseng saponin fraction isolated from American ginseng exhibited antifungal activity 38 and ginsenosides isolated from African Combretaceae exerted antimicrobial activity. 39 Rb1, but not Re or Rg1, rapidly accumulated in the roots of American ginseng upon infection with two fungi, Fusarium oxysporum and Fusarium solani, and effectively inhibited conidium germination of both Fusarium species; this implies that Rb1 functions as a chemical defense mechanism in American ginseng roots against pathogenic fungi.…”
Section: Chemical Defense Role Of Ginsenosides In Plantsmentioning
confidence: 99%